Pemodelan Sistem Dinamis Analisis Ketercapaian Reduksi Sampah Plastik Pada TPA Kota Surabaya - Sakti, Yuni Krida; Andi, Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The accumulation of plastic waste in the city of Surabaya has increased significantly every year. There are approximately 128,480 tons of plastic waste per year at the Benowo Surabaya Final Disposal Site (TPA), with a growth rate of around 1.29% per year. Meanwhile, the Surabaya Main Waste Bank (BSIS) in 2023, which partners with 600 Waste Bank Units (BSU) and 1190 individual customers, has reduced plastic waste by around 60 tons per year. In that year, BSIS reduced landfill plastic waste by 0.05%. The Surabaya City Government targets BSIS to reduce plastic waste accumulation by 1825 tons per year. This research aims to predict the achievement of this target, through dynamic system simulation modeling methods. By using analysis and calculations from secondary data, the average growth rate for BSU active partners is 11.5% per year and individual customers is 15.8% per year. Based on the results of dynamic system simulations, it is known that the target can possibly be achieved in 2030 with a reduction in plastic waste of 1,862 tons per year.